2014
DOI: 10.3109/02770903.2014.927483
|View full text |Cite
|
Sign up to set email alerts
|

Primary care visits for asthma monitoring over time and association with acute asthma visits for urban Medicaid-insured children

Abstract: Objectives To examine the association between numbers of primary care provider (PCP) visits for asthma monitoring (AM) over time and acute asthma visits in the emergency department (ED) and at the PCP for Medicaid-insured children. Methods We prospectively enrolled children 2–10 years-old during ED asthma visits. We audited hospital and PCP records for each subject for 3 consecutive years. We excluded subjects also receiving care from asthma subspecialists. PCP AM visits were those with documentation that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This approach is consistent with previous literature in regard to categorization of an emergency visit as “asthma related” according to documented asthma medications administered or prescribed at the visit. 30 Neither parental nor physician subjective impression of symptom severity was a factor in the categorization of revisits.…”
Section: Methodsmentioning
confidence: 99%
“…This approach is consistent with previous literature in regard to categorization of an emergency visit as “asthma related” according to documented asthma medications administered or prescribed at the visit. 30 Neither parental nor physician subjective impression of symptom severity was a factor in the categorization of revisits.…”
Section: Methodsmentioning
confidence: 99%
“…Studies suggested that follow-up visits help physicians to regularly evaluate asthma risk and alter treatment if required ( Nelson et al, 2014 ). These visits may also help in solving the issues of poor inhaler technique and failure to proper asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…Different findings are reported among the current literature regarding the association between patient PCP clinic follow-up compliance and ED returns/revisits [11, 19]. Some studies focusing on asthma patients revealed the value of urgent PCP follow-ups [22] and their impact on decreased ED returns [23], while others yielded opposite findings [24, 25]. Patients with Medicare/Medicaid tended to have more ED returns regardless of PCP clinic visits [26, 27].…”
Section: Discussionmentioning
confidence: 99%